2015
DOI: 10.1186/s12943-015-0421-2
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional crosstalk between PD-L1 expression and epithelial to mesenchymal transition: Significance in claudin-low breast cancer cells

Abstract: BackgroundThe T-cell inhibitory molecule PD-L1 (B7-H1, CD274) is expressed on tumor cells of a subset of breast cancer patients. However, the mechanism that regulates PD-L1 expression in this group of patients is still not well-identified.MethodsWe have used loss and gain of function gene manipulation approach, multi-parametric flow cytometry, large scale gene expression dataset analysis and immunohistochemistry of breast cancer tissue sections.ResultsInduction of epithelial to mesenchymal transition (EMT) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
212
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 233 publications
(234 citation statements)
references
References 38 publications
(48 reference statements)
9
212
0
1
Order By: Relevance
“…These findings suggest additional roles of PD-L1 in tumor biology, including epithelial to mesenchymal transition (EMT; ref. 49). …”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest additional roles of PD-L1 in tumor biology, including epithelial to mesenchymal transition (EMT; ref. 49). …”
Section: Discussionmentioning
confidence: 99%
“…Many recent studies have highlighted the critical role of PD-L1 in regulating the biological functions of cancer cells themselves, including cell proliferation, migration, metastasis, chemo/radio-resistance, and the promotion of epithelial to mesenchymal transition [9,10,18,21,23,[30][31][32]. It has been suggested that signal pathways such as JAK/ STAT1/IRF-1, MEK/ERK/STAT1 and PKD2 etc.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a study carried out by Alsuliman et al indicated that induction of epithelial to mesenchymal transition in human mammary epithelial cells up-regulated PD-L1 expression mainly through activation of the PI3K/AKT pathway [10]. In another study, it was shown that PD-L1 expression could induce epithelial-to-mesenchymal transition in renal cell carcinoma by activating the transcription factor SREBP-1c [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…74,75 PD-L1 is expressed in a significant number of TNBCs. [76][77][78][79][80] Early clinical trials are investigating the efficacy of anti-PD-1 pathway antibodies in TNBC. 20 Our unpublished data show that about 50% of TNBCs have positive PD-L1 staining in tumor or intratumoral stromal cells.…”
Section: Immune Checkpoint Inhibitorsmentioning
confidence: 99%